53 HEALTHCARE PROVISION FOR OLDER PEOPLE IN KILKENNY THROUGH THE IMPLEMENTATION OF THE INTEGRATED CARE PROGRAMME FOR OLDER PEOPLE. (18th November 2021) - Finegan, T; White, P J; Casey, B
Abstract: Background: An increase in the cost of healthcare provision is directly related to an ageing demographic nationally and internationally. It is, therefore, imperative that the system of health and social care provision for the older person is reformed. The Integrated Care Programme for Older People (ICPOP) envisages moving the locus of care from the acute system to primary and community health and social care. This research looks at the implementation and benefits of ICPOP from a clinicians and third sector organisations perspective. Methods: Semi-structured interviews were conducted with six clinicians within the acute and community healthcare systems and, with two representatives from older persons third sector organisations. The interviews were held online through conferencing software and recorded. They were transcribed manually to gain a greater understanding of what was said and the context. Using a grounded theory approach, quotes were extracted, clustered together into categories or themes and, through theoretical sampling and comparison an in-depth understanding was gained, and theory developed. Results: An organisational culture of innovative and collaborative practice is essential to the delivery of ICPOP as it leads to the empowerment of staff to develop integrated healthcare across disciplines and services. It is vital that funding for home support packages that provide both health and social care assistance with an adequate number of carers evenly distributed nationwide be provided. In addition, the 'Living Well at Home' piece of ICPOP with its important local community and social connectedness emphasis, needs to be sufficiently funded. Conclusion: A culture of collaborative and innovated practice of healthcare provision exists in Kilkenny. Implementation of ICPOP is commiserate with appropriate funding for, and even distribution of, home care support packages and carers, as well as support for services that combat loneliness and social isolation enabling older people to age well at home.